2013
DOI: 10.2214/ajr.12.8930
|View full text |Cite
|
Sign up to set email alerts
|

Dual–Time-Point FDG PET/CT for the Evaluation of Pediatric Tumors

Abstract: These data show that dual-time-point FDG PET/CT is useful in distinguishing malignant from benign processes in pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 17 publications
0
17
0
1
Order By: Relevance
“…Because patients underwent PET/CT first, the interval between imaging and radiotracer injection was longer for PET/MRI than for PET/CT (114 min vs. 61 min). Tissues with a high glucose turnover such as lung metastases are hypothesized to have an increased level of intracellular tracer trapping on delayed time-point images (24,25). Although we found a strong positive correlation in size measurements, there was a significant tendency for corresponding pulmonary lesions to measure smaller on PET/MRI than on PET/CT.…”
Section: Discussionmentioning
confidence: 48%
“…Because patients underwent PET/CT first, the interval between imaging and radiotracer injection was longer for PET/MRI than for PET/CT (114 min vs. 61 min). Tissues with a high glucose turnover such as lung metastases are hypothesized to have an increased level of intracellular tracer trapping on delayed time-point images (24,25). Although we found a strong positive correlation in size measurements, there was a significant tendency for corresponding pulmonary lesions to measure smaller on PET/MRI than on PET/CT.…”
Section: Discussionmentioning
confidence: 48%
“…Costantini et al, (26) found a considerable overlap in the early or delayed SUV max among most benign and malignant lesions.…”
Section: Dtp Pet/ct In Different Sitesmentioning
confidence: 96%
“…Also, Nakayama et al, (26,25) reported that In principle, RI-SUV max must have a merit of not being dependent on scale and is a useful index (2,27) . Some authors reported RI is a good predictor for diagnosis and prognosis, and is superior to only early imaging (28,29) .…”
Section: Dtp Pet/ct In Different Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the methods to overcome this problem is to use dualtime point PET imaging in the identification of malignant lesions. Various studies have reported the effectiveness of dual-time point PET imaging in different malignancies [11][12][13][14]. They suggested the retention index (RI), the percentage change between the 1-h SUVmax and the 2-h SUVmax, as a diagnostic criterion.…”
Section: Introductionmentioning
confidence: 99%